Effect of pomegranate peel extract on some pathogenic bacterial isolates (Journal of the College of Basic Education, 2022)
The effect of aqueous and alcoholic pomegranate peel extract was studied on different pathogenic isolates of Gram-negative and Gram-positive bacteria. These isolates included Staphylococcus aureus, Staphylococcus epidermis, Eschrichia coli, and Klebsiella spp. and Proteus spp. The extract showed a clear effect on all isolates, and this effect was compared with the effect of eight antibiotics, including Streptomycin, Vancomycin, Imipenen, Piperacillin, Gentamycin, Amoxicillin and Chlororamphenicol. It was shown through this study that the effect of the water and alcohol extract of pomegranate peels was more in some of these isolates than the effect of antibiotics. vitality.